2017
DOI: 10.1136/neurintsurg-2016-012849
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mean platelet volume is associated with poor outcome after mechanical thrombectomy

Abstract: Elevated MPV is an independent predictor of poor outcome in patients with acute anterior circulation stroke undergoing MT at 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…The observed reduction in mortality does not seem to originate from differences in adverse events such as severe hemorrhagic complications but from functional benefits of MT in patients who are at high risk of developing catastrophic infarcts under medical treatment alone. Overall, these results add to previous evidence showing that, at least in the early time window, patients with large vessel stroke benefit from MT despite having poor prognostic factors such as large lesions,7 8 poor collateral circulation,21 or systemic biomarkers of poor outcome 22 23. Although the results of ongoing randomized trials studying whether MT has a therapeutic effect in patients with large established lesions will be of utmost importance, these results suggest that the severity of the hypoperfusion should not be used to exclude patients from revascularization, at least in the early therapeutic window.…”
Section: Discussionsupporting
confidence: 65%
“…The observed reduction in mortality does not seem to originate from differences in adverse events such as severe hemorrhagic complications but from functional benefits of MT in patients who are at high risk of developing catastrophic infarcts under medical treatment alone. Overall, these results add to previous evidence showing that, at least in the early time window, patients with large vessel stroke benefit from MT despite having poor prognostic factors such as large lesions,7 8 poor collateral circulation,21 or systemic biomarkers of poor outcome 22 23. Although the results of ongoing randomized trials studying whether MT has a therapeutic effect in patients with large established lesions will be of utmost importance, these results suggest that the severity of the hypoperfusion should not be used to exclude patients from revascularization, at least in the early therapeutic window.…”
Section: Discussionsupporting
confidence: 65%
“…Several blood biomarkers representing different pathophysiologic pathways, such as copeptin plasma levels,19 hyperglycemia,20 or elevated mean platelet volume,21 measured on admission to the emergency room, have been demonstrated to be associated with clinical outcome, mainly in cohorts treated in the pre-MT era. There is a high potential of improving specificity of predictive scores such as MT-DRAGON using blood biomarkers, and further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies performed prior to 1995 found no relation, but 2 subsequent studies by Butterworth and Bath 11 and Greisenegger et al 12 found that an elevated MPV was related to a worse outcome in AIS patients. Moreover, Peng et al 13 reported that an elevated MPV was related to a poor outcome in AIS patients after mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…OR and 95% CI values were calculated after adjusting for the following potential confounders in a multivariable logistic regression model: age, NIHSS score at admission, and fasting glucose at admission. 13 , 24 A probability value of p <0.05 was treated as statistically significant. All of the statistical analyses were implemented using R software (version 3.3.1, The R Foundation, Vienna, Austria).…”
Section: Patient and Methodsmentioning
confidence: 99%
See 1 more Smart Citation